Operative Results for Ligamentous Ossification in the Thoracic Spine - Okajima, Keiichiro; Takano, Haruo; Urata, Shin'ichi; Maekawa, Kiyotsugu; Sakata, Hiroaki; Kawazoe, Yasuhiro (Orthopedics & Traumatology, 1996)
We surgically treated 20 cases of thoracic myelopathy caused by ossification of the yellow ligament (OYL) and combined OPLL. Subjects included 10 males and 10 females. The duration between the occurrence of symptoms and time of surgery ranged from 1 month to 2 years (average 8.3 months). The average age at surgery was 58 years. All patients had had laminectomy. We found difficulty in some cases in performing decompression of the ossified spinal lesions.